Korelasi Skor SOFA dengan Kadar Kortisol Darah pada Pasien Sepsis di RSUP Dr. M. Djamil Padang - Fahmi, Rahmadina Zesfira; Fadrian, Fadrian; Rikarni, Rikarni; Husni, Husni; Bilmahdi, Rohayat; Irramah, Miftah (Faculty of Medicine, Universitas Andalas, 2025)
Sepsis is a life-threatening organ dysfunction due to dysregulation of the body's immune response to infection. The Sequential Organ Failure Assessment score (SOFA score) is a diagnostic tool used to quantitatively and objectively assess the level of organ dysfunction. Sepsis as a stressor of systemic inflammation, causes an increase in cortisol secretion by the adrenals to target tissues, which suppresses inflammation. Objective: To determine the correlation between SOFA score and blood cortisol levels in sepsis patients at RSUP Dr. M. Djamil Padang. Method: Observational analytic study with a cross-sectional method. The sample consisted of 55 patients who had been diagnosed with sepsis. The data used was secondary data from medical records. The data were tested using the Spearman correlation test. Result: A correlation was found between the SOFA score and blood cortisol levels, yielding a correlation coefficient of r = 0.338 and a p-value of 0.012. Conclusion: There is a significant moderate correlation between SOFA scores and blood cortisol levels. Keywords: blood cortisol, sepsis, SOFA score